Peningkatan Mutu Ikan Keumamah Loin Aceh dari Cakalang (Katsuwonus pelamis) menggunakan Daun Kari (Murraya koenigii): Quality Improvement of Keumamah Loin Aceh Fish from Skipjack Tuna (Katsuwonus pelamis) using Curry Tree Leaves (Murraya koenigii) - Muhammad Nur Fajri; Nurjanah Nurjanah; Uju Uju (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Keumamah loin is a semi-wet wood fish with one to two days of sun drying, with soft meat texture, specific aroma and easily degradation in quality. Curry tree (Murraya koenigii) contain many bioactive compounds that serve as antioxidants. The Study was aimed to find out the effect of curry leaf extract, temperature, and drying time on the quality of keumamah loin and the effectiveness of curry tree as antioxidant. The study used complete randomized factorial design experimental method with different curry tree leaf extract levels (0% and 10%), temperature (40°С and 60°С), and time (8 hours and 12 hours). The observed parameters were proximate levels, water activity values (aw), and thiobarbituric acid (TBA). The results showed the use of curry tree leaves, temperature, and drying time did not have effect on proximate levels and water activity with protein 28.22–32.1%, fat 2.72–4.60%, ash 2.70– 4.52%, water 35.10–50.43% and water activity 0.84–0.87. However, the use of curry tree leaves affects the number of thiobarbituric acid (TBA). The use of 10% curry tree leaves, 40°С temperature, and 8 hours is the best treatment which has the lowest TBA 0.40±0.003 mg malondialdehyde/kg. The use of curry tree leaves, temperature, and drying time can inhibit the lipids oxidation process in the products of keumamah loin.